2014
DOI: 10.1016/j.gie.2014.01.050
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating endoscopic submucosal dissection: the suture-pulley method significantly improves procedure time and minimizes technical difficulty compared with conventional technique: an ex vivo study (with video)

Abstract: Background The lack of countertraction in endoscopic submucosal dissection (ESD) results in increased technical demand and procedure time. Although the suture-pulley method for countertraction has been reported, its effectiveness compared with the traditional ESD technique remains unclear. Objective To objectively analyze efficacy of countertraction using the suture-pulley method for ESD. Design Prospective ex vivo animal study. Setting Animal laboratory. Interventions Twenty simulated gastric lesions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 25 publications
(34 reference statements)
0
13
0
Order By: Relevance
“…Many approaches have been tested to accelerate and secure endoscopic resections. For the purpose of achieving better intraluminal tissue traction, various endoscopic devices have been designed, including external forceps, magnetic anchors, clips with attached strings, rubber bands, the EndoLifter, and the creation of a pulley system with clips to facilitate endoscopic traction [15,[21][22][23][24][25][26][27]. However, the optimal traction device for endoluminal surgery has not been identified so far.…”
Section: Discussionmentioning
confidence: 99%
“…Many approaches have been tested to accelerate and secure endoscopic resections. For the purpose of achieving better intraluminal tissue traction, various endoscopic devices have been designed, including external forceps, magnetic anchors, clips with attached strings, rubber bands, the EndoLifter, and the creation of a pulley system with clips to facilitate endoscopic traction [15,[21][22][23][24][25][26][27]. However, the optimal traction device for endoluminal surgery has not been identified so far.…”
Section: Discussionmentioning
confidence: 99%
“…A suture-pulley method to facilitate direct visualization of the submucosal layer during gastric ESD has also been shown to reduce the learning curve for trainees. 56,57 Traditionally, lack of counter-traction during ESD results in increased technical demand and procedure time. Results from this animal model study by Aihara and colleagues demonstrated significantly reduced procedure times (531 s vs 845 s; P < 0.001) with ease in technical difficulty.…”
Section: Reducing the Learning Curve: New Techniques And Technologiesmentioning
confidence: 99%
“…Results from this animal model study by Aihara and colleagues demonstrated significantly reduced procedure times (531 s vs 845 s; P < 0.001) with ease in technical difficulty. 56 Furthermore, among novice endoscopists new to ESD, the suture-pulley counter-traction method significantly decreased procedure time and technical demand. 57 Additional systems designed to provide counter-traction with clip placement attached to rubber bands have also been established to facilitate colorectal ESD.…”
Section: Reducing the Learning Curve: New Techniques And Technologiesmentioning
confidence: 99%
“…Several traction methods for ESD have been investigated to overcome the problem, such as percutaneous traction [ 5 ], clip with line [ 6 8 ], clip-and-snare [ 9 ], external grasping forceps [ 10 ], internal traction [ 11 , 12 ], suture-pulley [ 13 ], magnetic anchor [ 14 ], double-channel endoscope [ 15 ], double-endoscope [ 16 ], and robot-assisted method [ 17 ]. However, those traction methods need extra devices or equipment and may be invasive or difficult to control the pulley strength and direction or inconvenient to be operated.…”
Section: Introductionmentioning
confidence: 99%